Differences in health status of Slovak municipalities supplied with drinking water of different hardness values - Rapant, Stanislav; Letkovičová, Anna; Jurkovičová, Dana; Kosmovský, Viktor; Kožíšek, František; Jurkovič, Ľubomír (Environmental geochemistry and health, 2021)
This epidemiological study of ecological type deals with the analysis of relationship between drinking water hardness and health status of inhabitants of the Slovak Republic. This relationship was investigated in two groups of more than 50,000 inhabitants living in 53 different municipalities. The first group was supplied with drinking water with low hardness, and the second group was supplied with drinking water with increased hardness. The health status of the population of both groups was monitored by means of health indicators, which represented 15-year average values, for 1994-2008. We investigated four major causes of death, namely cardiovascular, oncological, gastrointestinal and respiratory tract mortality, and evaluated the average life expectancy. The health status of inhabitants supplied with drinking water with increased hardness was significantly better than the health status of people supplied with drinking water with low hardness. For example, the relative mortality for cardiovascular diseases, oncological diseases, digestive tract diseases and respiratory diseases was 56%, 62%, 128% and 121% higher in the population supplied with soft drinking water compared to the population supplied with hard water, respectively. In addition, life expectancy was more than 4.5 years higher in the population supplied with hard drinking water. Our observation confirms the findings of previous studies on relationship between the water hardness and human health.
Keywords: Health Status; lidé; velkoměsta; Hardness; Oncological diseases; tvrdost; chemické látky znečišťující vodu; Slovakia; Female; zdravotní stav; Water Pollutants, Chemical; Respiratory diseases; Humans; Drinking water; Slovenská republika; Gastrointestinal diseases; Cities; mužské pohlaví; Drinking Water; pitná voda; ženské pohlaví; Male; zásobování vodou; Water Supply; Cardiovascular diseases